ANALISIS PENGARUH RISIKO KREDIT TERHADAP TINGKAT PROFITABILITAS PADA PT.BANK NEGARA INDONESIA, Tbk PEKANBARU - Melina "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to examine the effect of credit risk, as measured by non performing loan to the level of profitability (return on assets) in the banking PT.Bank Negara Indonesia,Tbk.Sampling technique used is purposive sampling with criteria as PT. Bank Negara Indonesia,Tbk who provide financial report and traded during period 2006-2012. Obtained by amount sampel as much 28 in financial report kuartal since 2006 to 2012. Analysis technique used is simple linier regression.During research period show as data research was normally distributed. Based on multicolinierity test, heteroscedasticity test and autocorrelation test variable digressing of classic assumption on has not founded. Its indicate that the avaiable data has fulfil the condition to use simple linier regression model.Based on the result of the analysis, it is encountered that credit risk influenced negative but it is not significant toward profitability.Based on the above results, it is suggested: (1) it can be used as consideration in maximizing the level of profitability, (2) can increase an empirical and scientific evidence regarding non performing loan to the level of profitability, which can be in line with this research.Keywords : Credit Risk, Non performing Loan, Profitability, Return On Assets